Effects of Standardized Ileal Digestible Valine:Lysine Ratio on the Growth Performance and Economics of Finishing Pigs from 55 to 100 lb - M. A. Goncalves; J. Jacquez; M. D. Tokach; S. S. Dritz; K. J. Touchette; J. M. DeRouchey; J. C. Woodworth; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2015)
The objective of these experiments was to determine the effects of SID Val:Lys ratio in low CP and low lysine diets on the growth performance and economics of finishing pigs from 55 to 100 lb. In Exp. 1, a total of 1,134 gilts (PIC 337 × 1050, initially 68.8 lb BW) were used in a 19-d growth trial with 27 pigs per pen and seven pens per treatment in a randomized complete block design with pens blocked by initial average BW. There was a total of six dietary treatments: 59.0, 62.5, 65.9, 69.6, 73.0, and 75.5% SID Val:Lys ratio. In Exp. 2, a total of 2,100 gilts (PIC 327 × 1050, initially 56.6 lb BW) were used in a 22-d growth trial with 25 pigs per pen and 12 pens per treatment in a randomized complete block design with pens blocked by initial average BW. There was a total of seven dietary treatments: 57.0, 60.6, 63.9, 67.5, 71.1, 74.4, and 78.0% SID Val:Lys ratio. In both experiments, the intermediate Val:Lys levels were obtained by blending different proportions of the low and high Val:Lys diets. Responses measured at the pen level were analyzed using general linear and non-linear mixed models. Competing statistical models were: a broken-line linear ascending (BLL) model, a broken-line quadratic ascending (BLQ) model, and a quadratic polynomial (QP). Competing models were compared using Bayesian information criteria (BIC). In Exp. 1, ADG increased linearly (P = 0.009) with increasing SID Val:Lys ratio whereas ADFI only marginally increased (linear, P = 0.098) with no evidence for differences on F/G. Feed cost per pig, feed cost per lb of gain, and total revenue per pig increased (linear, P<0.009) with increasing SID Val:Lys ratio without evidence for differences in IOFC. In Exp. 2, ADG and ADFI increased (P<0.002) with increasing SID Val:Lys ratio resulting in an improvement in F/G (P<0.001). Similarly, increasing SID Val:Lys ratio increased feed cost per pig (quadratic, P<0.001), feed cost per lb of gain (linear, P<0.001), total revenue (quadratic, P<0.001), and IOFC (quadratic, P<0.001). In conclusion, the SID Val:Lys ratio to optimize performance ranged from 71.0% for minimum F/G to 74.4% for maximum ADG. However, feed cost per lb of gain was minimized at less than 57% SID Val:Lys ratio and maximum income over feed cost was estimated at 62.3% SID Val:Lys ratio with a plateau thereafter. Therefore, 99% of the optimum ADG and F/G were estimated at approximately 69% and 65% SID Val:Lys ratio, respectively.
Keywords: finishing pigs; growth; valine